Are we aiming for different metabolic targets in heart failure patients?. (25th November 2020) - Brito, J; Agostinho, J.R; Duarte, C; Silva, B; Pereira, S; Morais, P; Cunha, N; Rodrigues, T; Antonio, P.S; Santos, R; Nunes-Ferreira, A; Rigueira, J; et al.
Abstract: Introduction: Metabolic control plays an important role on major cardiovascular events (MACE) prevention. The 2019 ESC guidelines on dyslipidaemia management recommend tighter LDL-cholesterol (LDL-C) control in order to prevent cardiovascular events. However, it is not yet proven that thigh control of dyslipidaemia, glycaemic levels and body mass index (BMI) in Heart Failure (HF) patients (pts) have an impact on prognosis. Objective: To evaluate the impact of LDL-C, HbA1c and BMI values on HF pts mortality and MACE rates. Methods: Single centre study that included consecutive pts hospitalized for acute / decompensated chronic HF in a tertiary Hospital between January 2016 to December 2018 and followed for 12 months. The impact of LDL-C, HbA1c and BMI on mortality and MACE was assessed using Cox regression and Kaplan-Meier curve, after adjustment for age, sex, functional class and ejection fraction. A safety cut-off was established when any of these variables was deemed protective using ROC curve analysis. Results: Two hundred twenty-four patients (71.68±13.45 years, 63.8% males) were included. Eighty-four (37.5%) pts had type 2 diabetes, 39.7% had ischemic heart disease and the median left ventricular ejection fraction was 34% (IQR 25–49.5; 60.3% HFrEF; 13.8% HFmrEF; 22.3% HFpEF). The median BMI was 25.4 kg/m 2 (IQR 23.1–30.5), HbA1c, 6.4% (IQR 5.6–6.8) and LDL-C, 89.5 mg/dL (IQR 64–106); 145 (64.7%) pts were medicated with statins. The overall mortality and MACE rates during follow-up were 16.1% and 21.0%, respectively. According to the CV risk classification 39.7% pts were at very high risk and 19.6% pts at high risk. On multivariate analysis HbA1c (HR 1.5 IQR 1.1–1.9; p=0.007) and female sex (HR 9.453 IQR 2.4–37.2; p=0.001) were independent predictors of mortality, whereas LDL-C (OR 1.05 IQR 1.022–1.075; p<0.001) and BMI (OR 1.23 IQR 1.075–1.404; p=0.002) were independent protective factors. LDL-C and BMI had no effect on MACE rates, although HbA1c was an independent predictor of MACE (HR 1.27 IQR 1.03–1.57; p=0.026). For high and very high-risk pts there was still a protective trend on mortality, although non-significant, for higher levels of LDL-C (OR 1.04 IQR 0.99–1.075; P=NS). Protective LDL-C cut-off were estimated for the whole population (LDL-C 88mg/dL; AUC 0.819; sn 56.6%, sp 100%) and for the high and very-high CV risk pts (LDL-C 84mg/dL; AUC 0.815; sn 59.3%; sp 100%). A BMI safety cut-off for mortality of 25.75 kg/m 2 was found (AUC 0.627; sn 61.2%; sp 58.3%). Conclusion: This study supports the theory of the obesity and LDL-C paradox in HF. Lower LDL-C and BMI increased mortality and there is no trade-off effect on MACE rates, supporting the idea that LDL-C and BMI should not be aggressively addressed in HF pts. In our cohort a cut-off level of LDL-C below 88mg/dL is associated with higher mortality. On the other hand, diabetes should be actively treated as HbA1c predicts death and MACE in HF pts. Funding Acknowledgement: Type of funding source: None